Effects of different feeding regimens on milk fatty acid composition and milk flavor from the perspective of regional resource utilization. (19th November 2019) - Yayota, Masato; Tsukamoto, Mana; Kato, Rie; Ohtani, Shigeru
Abstract: Feed is a primary factor affecting different milk components and creating a specific milk flavor. Dairy farms in different regions often depend on different feed resources and feeding regimens. This study aimed to evaluate the effect of completely different feeding regimens on the milk fatty acid (FA) profile and milk flavor. Eight lactating Holstein cows were assigned to one of two distinct feeding regimens, one grass silage‐based diet (GS) and one by‐product‐based diet (BP), using a switchback design with three periods of 28 days each. A sensory test of the pasteurized milk was conducted using the paired preference method. Dry matter, crude protein and total digestible energy intake were similar between the groups. There was also no difference in daily milk yields, milk fat, protein, lactose and solids‐not‐fat contents between the groups. Milk FA content with chain lengths C12 –C14:1, C16 and C16:1 cis and the saturated fatty acid (SFA) content were significantly higher in the GS group than in the BP group. In contrast, the milk FA content with chain lengths C18 and C18:1 cis –C18:2 and the unsaturated fatty acid (UFA) content, including mono‐UFA (MUFA) and poly‐UFA (PUFA), were significantly higher in the BP group than in the GS group. The different feeding regimens did not affect milk sensory properties, including aroma, palatability, aftertaste, texture, body and sweetness. Using food by‐products that contain relatively high levels of PUFAs resulted in PUFA‐rich milk. However, even if using a distinct feeding regimen based on conserved or by‐product feeds, it may be difficult to create characteristic milk with an original flavor that is clearly identified by consumers.